The Impact Of Consumer Time Sensitivity On Product Development Process Choices In A Competitive Market - Yessica Amelia; Ngadi Permana; Farah Qalbia (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This study aims to explore the impact of consumer time sensitivity on product development process choices in a competitive market. By analyzing the existing literature, this study identifies two main approaches to product development: concurrent processes and sequential processes. Concurrent processes allow companies to accelerate product launches, while sequential processes reduce the risk of irreversible upfront investments. The study found that consumer time sensitivity encourages companies to adopt concurrent processes, especially in dynamic markets. In addition, asymmetry in competition, where companies have different product approval probabilities, affects the development strategy carried out. Government policies also play a role in supporting investment in product development through subsidies, although this can lead to unwanted side effects. This research provides important insights for managers and stakeholders in formulating effective product development strategies and underscores the importance of understanding consumer behavior in corporate decision-making.